Screening of muslimah's prayer hall in mosque / Nurul Hanis Mustafa Kamal - Mustafa Kamal, Nurul Hanis (2014)
Following the Islamic reform movement, there are some issues on women's prayer space. Masjid in UiTM campus is separated the women prayer space by solid plain curtain. As for women who pray behind the Imam, they can't see the Imam or see those who are in front of them. The space for the women also not comfortable and inconvenient as the women's space can be visible by the men from the outside of the mosque. Meanwhile in Islam tradition, Jama ·ah means a congregation of people who are praying behind one Imam in continuous lines without any barrier or interruption.